Carga Viral de Influenza a H1n1pdm09 e Influenza B em Pacientes Hospitalizados e Ambulatoriais do Complexo Hospitalar Hospital São Paulo/Unifesp - Alves, Vitoria Rodrigues Guimaraes [UNIFESP] (2020)
Influenza continues to be a major cause of morbidity and mortality worldwide. The aim of the study was to evaluate and compare the viral loads between Influenza B and Influenza A(H1N1)pdm09 viruses, as well as to investigate mutations, in the PA protein, of type B strains in hospitalized patients (HP) and outpatients (OP), positive for Influenza treated at Hospital São Paulo. For analysis, patients were divided into groups: (i) Immunodepressed (ID); (ii) Immunocompetent (IC), composed of HP and OP and asymptomatic (AS). To calculate the viral load, a one-step RT-qPCR assay was performed at the NS1 and M gene (Influenza B and A, respectively), with the human RNAseP gene as an endogenous control and normalizer of the threshold cycle (Ct) values. The viral load was calculated in Log10 copies of RNA/mL. In general, the highest detection rate occurred in the age range of 2-18 years (5-11 and, 2-18 years, for types A and B, respectively). For Influenza B, there was no significant difference in viral loads between groups of patients (ID, OP and HP) and ages. PA sequencing protocol was 50% successful. Pathogenicity and viral resistance mutations were not found. For H1N1pdm09, we observed a significant difference between the viral loads of AS vs. symptomatic. AS patients accounted for 9% (15/162) of infection cases. Patients with comorbidities and severe clinical symptoms, under treatment with antiviral, had a late viral clearance. Influenza B infection rates follow an age pattern, however, viral load does not seem to contribute to the frequency or outcome of the disease. The viral load of H1N1pdm09 was associated with the presence of symptoms. Contrarily to what was observed for Influenza B, H1N1pdm09 positive patients with underlying diseases and severe clinical symptoms can be considered for prolonged antiviral treatment for a complete viral clearance.